2019
DOI: 10.1172/jci.insight.129380
|View full text |Cite
|
Sign up to set email alerts
|

Precocious chondrocyte differentiation disrupts skeletal growth in Kabuki syndrome mice

Abstract: At time points where the variance of the random effect was estimated equal to 0, we fit a fixed-effects model using the genotype only. Finally, within each time point, we performed the post hoc pairwise comparisons among the 3 different genotypes using the emmeans R package, and we corrected for multiple testing using Tukey's adjustment method.Study approval. All experiments using laboratory mice were performed in accordance with the NIH Guide for the Care and Use of Laboratory Animals

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

5
53
6

Year Published

2020
2020
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 35 publications
(64 citation statements)
references
References 69 publications
(84 reference statements)
5
53
6
Order By: Relevance
“…Herein, we detail the immunological phenotype of a haploinsufficient mouse model of KS (Kmt2d 1/bGeo mice) in which the enzymatic domain of 1 copy of Kmt2d has been replaced with a bGeo cassette. This mouse reliably models KS phenotypes, [8][9][10] and we show that many of the immune phenotypes observed in patients (IgA deficiency, impaired response to vaccination, and splenomegaly) are also recapitulated in these mice. [11][12][13] We also uncover novel phenotypes including decreased size and numbers of Peyer patches (PPs), as well as abnormalities of the peritoneal cavity, bone marrow, and intestinal B-cell/plasma-cell compartments.…”
mentioning
confidence: 68%
“…Herein, we detail the immunological phenotype of a haploinsufficient mouse model of KS (Kmt2d 1/bGeo mice) in which the enzymatic domain of 1 copy of Kmt2d has been replaced with a bGeo cassette. This mouse reliably models KS phenotypes, [8][9][10] and we show that many of the immune phenotypes observed in patients (IgA deficiency, impaired response to vaccination, and splenomegaly) are also recapitulated in these mice. [11][12][13] We also uncover novel phenotypes including decreased size and numbers of Peyer patches (PPs), as well as abnormalities of the peritoneal cavity, bone marrow, and intestinal B-cell/plasma-cell compartments.…”
mentioning
confidence: 68%
“…A recent study of the skeletal phenotype in a KS-1 mouse model indicated that Kmt2d haploinsufficient mice have precocious chondrocyte differentiation and disrupted skeletal formation [135]. The mice have bowing of the ventral aspect of the skull and shortened long bones compared to wild-type controls, findings which recapitulate aspects of the human disease phenotype.…”
Section: Craniofacial Developmentmentioning
confidence: 95%
“…KS mice phenotypes are comprised of skeletal growth retardation and decreased length and weight as a cause of shortened long bones [ 30 ]. These findings are also seen in KS patients [ 31 ].…”
Section: Growth and Endocrinologymentioning
confidence: 99%
“…Abnormal SOX9 expression (for instance, as a result of KMT2D variant) prevents the differentiation of chondrocytes into osteoblasts, ultimately causing too many chondrocytes and too few osteoblasts in the skeletal system. This probably causes improper growth, specifically growth retardation in KS (shortening of long bones and ineffective bone formation) [ 30 ].…”
Section: Growth and Endocrinologymentioning
confidence: 99%